Complete mitogenome of the shortfin spiny eel, Notacanthus bonaparte (Elopomorpha; Notacanthiformes). Issue 2 (2nd April 2020) - Barros-García, David; Gomes-dos-Santos, André; Machado, André M.; Castro, L. Filipe C.; de Carlos, Alejandro; Bañón, Rafael; Bruno, Isabel; Arronte, Juan C.; Froufe, Elsa
Abstract: Deep-sea fish taxa are elusive, difficult to study, and in multiple cases, represent taxonomic conundrums. Here, we sequenced the complete mitogenome of the shortfin spiny eel, Notacanthus bonaparte, for the first time using low coverage Illumina Paired-end (PE) sequencing. The shortfin spiny eel belongs to the order Notacanthiformes, a relatively unknown taxon of deep-sea marine fishes mostly benthopelagic and bathydemersal. The total length of the assembled mitogenome is 16, 623 bp and displays the expected gene orientation for vertebrate mtDNA. Phylogenetic analyses combining all the available mitogenomes of the order Notacanthiformes were performed. The position of N. bonaparte as a member of the Notacanthidae family was confirmed. This mitogenome provides a valuable baseline for future research of N. bonaparte .